PENGATURAN TENTANG FEMISIDA DALAM HUKUM PIDANA INDONESIA (KAJIAN PERBANDINGAN UU HAM DAN UU TPKS) - Salamor, Yonna Beatrix; Purwanti, Ani; Rochaeti, Nur (Faculty of Law, Universitas Pasundan, 2024)
Femicide is the taking of the life of a woman or girl because she is a woman or because of gender-based violence. The type of femicide that is often found in the field is intimate femicide, which is committed by people who have a relationship with the victim. Indonesia has various laws and regulations that regulate the protection of women and girls, including the Human Rights Law, the Child Protection Law, the Domestic Violence Law, and the TPKS Law, but the specific regulation of femicide has not been explicitly described in these various laws and regulations. This research uses a normative juridical method, which is legal research that places the law as a building system of norms that are studied through principles, norms, rules of laws and regulations, agreements, and doctrine. Based on the results of the discussion, it is found that there are 7 types of femicide that occur in the society, including the Indonesian society. the regulation of femicide has not been explicitly regulated in the Human Rights Law or in the TPKS Law. The Human Rights Law regulates the protection of human rights including women's rights in Article 45. Meanwhile, the TPKS Law further regulates the types of femicide that occur in Indonesia such as gender-based sexual violence, pornography, dating and domestic violence. Keyword: Femicide, Human Rights, Sexual Violence Crime.